Oil Price and Real GDP Growth of Ecuador: A Vector Autoregressive Approach - PALADINES, Jesser (Journal of Economics and Political Economy, 2017)
Abstract. Ecuador is an oil exporter country but it is also an importer of oil derivatives products, in this research the relationship between the world average price of oil and the GDP per capital of Ecuador is studied, taking annual data of both from 1980 to 2015 and using the methodology of Vector Autoregressive (VAR), it is concluded according to the Impulse Response Function that a positive shock on the price of oil affects positively the GDP growth of Ecuador for 2 unit times and then returns to its natural state later. This must be explained because Ecuador is a net exporter of oil, the VAR model showed itself stable, in addition it was demonstrated that there is a causal relationship of GDP to the Price according to methodology of Toda-Yamamoto. Keywords. Average Oil price, GDP, VAR, Ecuador. JEL. C32, 040, F20.